The reflections of young deaf adults regarding transition the from school to higher education and employment within the Western Cape - Mitchell, Leilani (My University, 2016)
Only a small number of Deaf school-leavers in South Africa enter higher education institutions (DeafSA, 2009). There does not seem to be an incentive to encourage Deaf school-leavers to enter higher education which contributes to the 90% unemployment rate of Deaf adults in South Africa (DeafSA, 2009). Deaf learners do not always seem to have opportunities for further study due to poor literacy skills. Deaf school leavers appear inadequately prepared for further education and employment when they leave high school and experience difficulty with communication and socio-emotional adjustment in the hearing world. This study explored the preparedness of young deaf adults for further education and employment within the Western Cape by describing the reflections of Deaf school-leavers regarding their transition from school to higher education and vocation. Focus group interviews and in-depth individual interviews were conducted with 19 Deaf participants between the ages of 21 and 25 who use SASL as their primary mode of communication and have attended a signing school for the Deaf in the Western Cape. The services of two SASL interpreters were used and the data collected were analysed using a thematic analysis. The findings of this study point to possible strategies that may facilitate the transition of the Deaf school leaver to higher education and vocation in the Western Cape. The data obtained in this study indicated a need for improved academic preparation of Deaf learners; an increase in educators of the Deaf that are fluent in SASL; an increase in SASL interpreters at higher education institutions and stronger transition programs at schools for the Deaf in the Western Cape. Moreover, participants in this study indicated a need for financial assistance for Deaf students to further their education and expressed the need for Deaf awareness and sensitization training of employers, employees, lecturers and fellow students of the Deaf in the Western Cape. Furthermore, the findings of this study suggested assistance from job placement officers with regard to integration and socialization of deaf employees in the workplace.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Arts in Audiology in the Faculty of Humanities, University of the Witwatersrand, Johannesburg March 2016.
Keywords: Deaf students--Western Cape; Deaf youth--Western Cape; Hearing impaired